Motivation, language identity and the L2 self [ - Dèornyei, Zoltaan; Ushioda, Ema (Bristol, UK. : Multilingual Matters, 2009)
With contributions by leading European, North American and Asian scholars, this volume offers a comprehensive anthology of conceptual and empirical papers describing the developments in L2 motivation research that involves the reframing of motivation in the context of contemporary notions of self and identity
Description based on print version record
Title from e-book title screen (viewed Mar 16, 2009)
Includes bibliographical references and indexes
Keywords: Identity (Psychology); Motivation in education; Second language acquisition; Self